Strategies for weed suppression in aerobic rice cultivation - Anwar, Md. Parvez (2012)
Aerobic rice, a promising water-wise rice production system, is highly vulnerable to weed invasion which demands an effective weed management strategy. This study was, therefore, initiated aimed at developing a more comprehensive integrated weed management system for aerobic rice. Thirteen rice varieties were evaluated for their weed suppressive ability and productivity under aerobic soil conditions. Rice varieties differed widely in their weed suppressive ability and yield. AERON 1 exhibited very strong weed suppressive ability and highest yield potential closely followed by AERON 4. Two seeding methods and three seeding rates were tested to identify suitable method and seeding rate in terms of weed suppression and yield of AERON 1. Weed density and dry weight decreased gradually with increased seeding rate but were independent of seeding methods. Row seeding produced higher grain yield compared to broadcast seeding. Increasing seeding rate up to 300 seeds/m2 was found worthwhile to reduce weed pressure without sacrificing rice yield. An attempt was made to explore the possibility of adopting seed priming technique as a tool for weed management. Seed priming considerably improved germination attributes, weed suppressive ability and yield of AERON 1. Zappa® priming was the best in terms of weed suppression and yield. In herbicide screening trial, eight herbicide formulations were applied in different combinations. Most of the herbicides provided excellent weed control. In terms of weed control efficacy and cost effectiveness, Cyhalofop-butyl + Bensulfuron followed by (fb) Bentazon/MCPA performed the best. Among others, Bispyribac-sodium fb Bentazon/MCPA and Pretilachlor/safener fb Propanil/Thiobencarb also exhibited high weed control efficacy and net benefit. All the herbicides showed high selectivity to rice plant. An attempt was made to identify the critical period of weed control (CPWC) of AERON 1 in two different seasons. The CPWC varied between seasons. Based on the 5% yield loss level, the CPWC in main and off seasons were 7 to 49 and 7 to 53 days after seeding (DAS), respectively, while at 10% yield loss level, the same were 23 to 40 and 21 to 43 DAS, respectively. To develop an integrated weed management package, weed competitive rice variety AERON 1, higher seeding rate of 300 seeds/m2 and seed priming by Zappa® were incorporated. As a consequence of integrating different agronomic practices, lower weed pressure and higher weed control efficacy were evident in this study compared to the previous study. Weed management through Cyhalofop-butyl + Bensulfuron or Bispyribac-sodium or Propanil/Thiobencarb fb Bentazon/MCPA emerge as highly effective and most economic package. Application of Pretilachlor/safener fb Propanil/Thiobencarb fb Bentazon/MCPA also may be considered. Despite being less remunerative, spraying with any of the aforesaid early-post emergence herbicides in rotation followed by a manual weeding may be recommended for long-term sustainability of aerobic rice system.